The running machine : the invention of the very first bicycle - Negley, Keith (Balzer + Bray, an imprint of HarperCollins Publishers, 2024)
"Before there were trains, or cars, or planes, people rode horses to travel from place to place. Then came the Year without a Summer in 1816, when a cloud of volcanic ash blocked the sun and crops withered across half the world. With no oats to eat, horses grew too weak to walk. Everyone despaired--how would they get around? But one day, a young forester had a bright idea in the darkness . . . Inspired by true events, 'The Running Machine' shows how resilience in the face of adversity can lead to something wondrous"--Provided by publisher.